The Construction of Mohammad Daʻwah to Umma Al-Daʻwah in Hadiths Of Kutubus-Sittah - Fery Hidayat, Yogi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Islamic Daʻwah refers to the activities of teaching Islamic Sharia and preaching to people to believe in God. Da'wah contains two main elements: Amar Ma'ruf (teaching people to do good) and Nahi Munkar (preventing humans from performing wrongdoings). A preacher will face various risks in teaching the people about Amar Ma'ruf Nahi Munkar. Therefore, this study was performed to explain the construction of daʻwah to Umma al-daʻwah by Rasulullah Saw, as mentioned in the content of hadiths in Kutub al-sittah concerning Daʻwah to Umma al-daʻwah. This descriptive qualitative study regarded data from hadith texts. The data were first reduced and analyzed to obtain broad conclusions. Then, data were grouped, categorized, and analyzed by using content analysis method. The hadith texts describe Mohammad Prophet's Daʻwah as promoting monotheism, being gentle, polite, and avoiding wrongdoing; making things easier instead of complicating them; providing good news instead of fear-mongering messages; working collaboratively and avoiding disagreements; and gradually teaching the Sharia.